Two new spider species of the family Dysderidae (Araneae) from Turkey. Issue 2 (2nd April 2016) - Varol, M. İsmail; Akpınar, Adile
Abstract : Two new species of the spider family Dysderidae, Harpactea pugio sp. n. and Dysdera tezcani sp. n. are described from the Aegean region of Turkey. Detailed morphological descriptions and diagnoses are presented together with figures of the copulatory organs. The two new species are compared with closely related species. http://www.zoobank.org/ urn:lsid:zoobank.org:pub:23253E90-67F4-4B18-B9FE6485B8DD0796